Determining the effectiveness of stress management program by using hair cortisol concentration - Sundram, Bala Murali; Shaharudin, Rafiza; Mohamad, Nadia; Pahrol, Muhammad Alfatih; Omar, Affandi; Sevaratnam, Gogillan; Kumareswaran, Suriya; Rajendran, Kamesh (Intelektual Pustaka Media Utama, 2024)
Many studies have shown that healthcare workers are exposed to higher levels of stress than other occupations. However, little research has been conducted on the use of biomarker tools to assess chronic stress and assess the effectiveness of stress management programs for healthcare workers. The aim of this study was to measure the effectiveness of a Stress Management Program by measuring Depression Anxiety Stress Scale (DASS-21) scores and hair cortisol concentration (HCC) levels of healthcare workers in public healthcare facilities. This study was a three-group, quasi-experiment study with pre- and post-study assessment sessions. A total of 119 healthcare workers (28 from Group A, 21 from Group B, and 70 from Group C) were followed for 6 months. Significant favorable intervention effects on DASS-21 scores were found in Group A (Effect size =0.6) as compared to Group B (Effect size=0.2) and Group C (Effect size =02) at the end of the program. Time and group interaction effects were examined using the repeated measure ANOVA test in which there was a significant group *time interaction and effect size of 0.2 (p-value <0.01) across all the groups with a reduction in hair cortisol concentrations following the program. The study showed that stress management under healthy communities, building the nation (KOSPEN PLUS) program was successful in reducing stress levels, as seen through a decrease in both stress scores and hair cortisol levels. This is the first study in Malaysia to use hair cortisol as a biomarker for stress management, suggesting its reliability.